P181 Transition arrangements for young adults with asthma: uk national survey. (15th November 2016) - Lee, CWJ; Patel, BR; Nagarajan, T; James, H; Burhan, H; Jones, GH
Abstract : Introduction: Transition of young adults (YA) from specialist paediatric to adult services is an active process that requires specific management and planning and does not merely represent the transfer of care as a single event. In other chronic diseases (e.g. Cystic Fibrosis; T1DM) it is well acknowledged that clinical outcomes improve when this process is well organised and where this is lacking the risk of non-adherence to treatment and loss of disease control increases. BTS guidelines 1 clearly recommend a coordinated approach when transitioning YA in an asthma setting. Despite the importance of this process, little information is available on transition arrangements in asthma services. Methods: An online survey was sent to 105 trusts with adult asthma services in all parts of the UK to establish their transition arrangements. Results: Of the 43 responding centres (District General Hospital n = 20), only 60% had a designated lead (n = 26) and less than half made any form of specific arrangements for transition (n = 18). University Hospital trusts were more likely to have transitional care arrangements in place (n = 11/22) than District General Hospitals (n = 6/20). In those centres that did run joint clinics (n = 16), in the majority of cases this only involved adult team members attending paediatric clinics (n = 10). Most centres (n = 25) expected ≤5 patients to transition each year and over 90% (n = 37) did not initiate contact with YA until they were ≥15 yrs old. Only a third of centres delayed transition if YA were not perceived to be ready (n = 15) or remained in full time education (n = 15). Overall less than a third of respondents (n = 13) were satisfied with their transition arrangements. Conclusions: Our survey reveals for the first time the wide variation in approaches to transition in asthma clinics across the UK. Our data suggests that currently most centres are not committing the recommended resources towards this process, no doubt hampered in part by the relatively small numbers of young adults with asthma transitioning each year. Reference: British Thoracic Society. BTS/SIGN Asthma guideline . 2014. https://www.brit-thoracic.org.uk/document-library/clinical-information/asthma/btssign-asthma-guideline-2014/ (accessed 28 June 2016).